Beethoven's 32 piano sonatas a handbook for performers - Gordon, Stewart 1930- (Oxford University Press, 2017)
"The thirty-two piano sonatas of Ludwig van Beethoven comprise one of the most important parts of the piano literature, yet true mastery of these works can be elusive to even the most seasoned performer. With years of experience performing and teaching the literature and intimate knowledge of the works, their history and context, renowned pianist and pedagogue Stewart Gordon guides today's pianist performer through each of the thirty-two sonatas in stunning detail."--Page 4 of cover.